2011
DOI: 10.1002/9781444342901
|View full text |Cite
|
Sign up to set email alerts
|

The Handbook of Language Socialization

Abstract: 'tion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(5 citation statements)
references
References 45 publications
0
2
0
3
Order By: Relevance
“…The FLP of these transnational families can be derived through the observation of their intergenerational interactions and their statements. Since these families interact using asymmetrical resources in three languages (two familial and one national), we might expect the adults to exercise linguistic authority (Spolsky, 2009;Duranti, Ochs and Schieffelin, 2011) over the youngest generation in order to maintain their heritage languages. However, we haven't witnessed linguistic authority but collaboration, carried out with mutual and reciprocal caring.…”
Section: Discussionmentioning
confidence: 99%
“…The FLP of these transnational families can be derived through the observation of their intergenerational interactions and their statements. Since these families interact using asymmetrical resources in three languages (two familial and one national), we might expect the adults to exercise linguistic authority (Spolsky, 2009;Duranti, Ochs and Schieffelin, 2011) over the youngest generation in order to maintain their heritage languages. However, we haven't witnessed linguistic authority but collaboration, carried out with mutual and reciprocal caring.…”
Section: Discussionmentioning
confidence: 99%
“…This practice also enables us to clarify for ourselves how we use a word. Indeed, while language socialization is an active process that spans from language acquisition in early childhood to learning specialized ways of speaking (Duranti et al, 2011), it is largely implicit (suggested though not directly stated). Only a minority of words and meanings are acquired "metalinguistically" via explicitly talking about language (e.g., when we ask someone to define a word).…”
Section: Writing As Socializationmentioning
confidence: 99%
“…Ezek az egyes közösségekben jellemző kulturális sajátosságok, szokások, gyakorlatok feltárását helyezik a központba, ezek keretében vizsgálják a nyelvelsajátítást és a gyermekekkel folyó diskurzusokat. Ide tartoznak a pragmatikai fejlődés kutatását és a fejlődéses szociolingvisztikát megalapozó első, nagyhatású munkák, különösen Ochs, Schieffelin, Ervin-Tripp, Snow és Heath kutatásai (például Ervin-Tripp & Mitchell-Kernan, 1977;Ochs & Schieffelin, 1983;Heath, 1983;Pan & Snow, 1999;Duranti et al, 2012). Ők különböző kultúrákban -például a Pápua Új-Guineában élő kaluliknál, a szamoa társadalomban, valamint holland és amerikai közösségekben -figyelték meg a mindennapi élet helyzeteit, főleg az anya és kisbabája, illetve a gyermekek és felnőttek közti társalgásokat, és a nyelvelsajátítás számos sajátosságát és különböző útját tárták fel.…”
Section: Kutatási Előzményekunclassified
“…Ebben nagy szerepe van egyrészt a szociokulturális környezetnek, a szülők, gondozók beszédének, interakciós aktivitásának; másrészt egyéni, genetikai eredetű tényezőknek is. Az antropológiai keretű kutatások számos példán mutatták be a szociokulturális tényezők hatását a konverzációs készségek alakulására, többek között a gyermekek szóátvételi stratégiáira, udvariassági nyelvhasználatára vagy beszédaktusaira (Ochs & Schieffelin, 1983;Duranti et al, 2012). Szalai (2013) például feltárja, hogy az átok, átkozódás egy fajtáját a gábor cigányok kifejezetten pozitív és fontos beszédaktusként használják -többek között a gyermekbecézés, a tiszteletadás vagy az udvarias kínálás eszközeként -, és használatát a felnőttek a gyermekekkel kiskoruktól kezdve gyakorolják (Szalai, 2013).…”
Section: A Társalgási Készségek Fejlődése éS Tényezőiunclassified
See 1 more Smart Citation